Urban Tier Variations in Public Compliance During Pandemics: Survey Evidence from China on COVID-19 - Ben Ma; Yanbo Wang; Zongfeng Sun; Linxu Zhu (Journal of Homeland Security and Emergency Management, 2026)
Abstract Investigating tier-specific public compliance with COVID-19 containment measures is essential for developing effective post-pandemic strategies. This study examines compliance behaviors across first-, second-, and third-tier cities in three northern provinces of China, utilizing survey data from 985 respondents. The Kruskal–Wallis test, supplemented by a post-hoc Dunn’s test, identifies significant differences in compliance levels, with third-tier cities exhibiting notably higher compliance than first-tier cities. Grouped nested regression models reveal distinct drivers of compliance across urban tiers. In first-tier cities, psychological factors – such as risk perception and trust in government – play a more salient role, whereas in third-tier cities socially embedded influences, including community norms and peer behavior, are more prominent. In second-tier cities, police effectiveness exerts only a marginal influence, suggesting that more diffuse and complex factors are at play. These findings highlight the importance of tailoring strategies to the unique psychological and social dynamics of each urban tier, providing valuable insights for managing future public health crises.